Analysis of the Implementation of Green Building Technology in Building Maintenance - Dimas Wahyu Kurniawan; Silvia Yulita Ratih; Fahmi F. Dalimarta; Adhi Susilo (Jurnal Ilmiah Teknik, 2026)
Hospitals are resource-intensive facilities with continuous operations that result in high energy and water consumption, making the implementation of green building technology essential to improve environmental performance during the operational phase. Objective: This study aims to identify the energy, water, and material efficiency measures implemented at RSUD dr. Soeratno Gemolong, Sragen, and to evaluate the level of efficiency achieved based on EDGE (Excellence in Design for Greater Efficiencies) standards. Methods: The research employed an applied evaluative approach by collecting primary and secondary data through direct observation, interviews, documentation review (as-built drawings and material data), and literature review. The collected data were analyzed using the EDGE application and compared with EDGE benchmarks and relevant Indonesian regulations. Findings: The results indicate that baseline energy efficiency was 19.85%, slightly below the EDGE minimum requirement of 20%, but increased to 24.09% after targeted improvements such as reducing building envelope air infiltration and improving cooling system efficiency. Water efficiency reached 25.75%, and material efficiency achieved 34%, both exceeding the EDGE minimum standard. Implications: These findings demonstrate that EDGE-based evaluation can support maintenance-driven optimization strategies in hospital buildings and provide practical guidance for facility managers and policymakers in prioritizing high-impact efficiency interventions. Originality/Value: This study provides an integrated empirical assessment of energy, water, and material efficiency (EEM, WEM, MEM) in an operational public hospital, showing how targeted improvements can shift energy performance from near-compliance to compliant status within the EDGE framework.